Efektivitas Penggunaan Modul Larutan Penyangga Berbasis Discovery Learning terhadap Hasil Belajar Siswa Kelas XI MIA SMAN 7 Padang - Yerimadesi Yerimadesi; Ananda Putra; Ririanti Ririanti (JURNAL EKSAKTA PENDIDIKAN (JEP), 2017)
Quasi experiment research with randomized control posttest group only design was carried out to determine the effectiveness of using a discovery learning based module on students learning outcome. Grade XI MIA-1 to MIA-4 students academic year 2015/2016 in SMAN 7 Padang became population of this study. Through cluster sampling technique, grade XI MIA-1 and grade XI MIA-4 were chosen as experiment and control classes respectively. The experiment class was taught using discovery learning based module in buffer solution topic while the control class was taught the same topic conventionally without the module. Research instrument used was cognitive learning outcome test with multiple choice form. Data showed that the mean test score of experiement class (78.84) was higher than that of control class (71.09). Normality and homogenity test proved that both classes were homogeneous and normally distributed. T-test, as data analysis taken, showed that t-count (3,51) is bigger than t-table (1.67). Thus, it could be concluded that students’ cognitive learning outcome in experiment class is significantly higher than that in control class. The use of discovery learning-based module in buffer solution topic was effective in increasing learning outcome of grade XI MIA students in SMAN 7 Padang.